Enhancing Observation and Questioning Skills in Rural Science Education - Maria Senisum; Ambros Leonangung Edu (Postgraduate, University of Mataram, 2023)
This study aims to determine the influence of enhancing observation and questioning skills on learning outcomes, and to describe the relationship between these skills and science learning outcomes. The study included 86 fifth-grade students from four distinct rural elementary schools. Participants were divided into control and experimental groups. The collected data encompassed learning outcomes and metrics on observation and questioning skills. The impact of advancing observation and questioning skills was evaluated using an independent sample t-test at a 5% significance level. The Pearson correlation was employed to discern the relationship between these skills and learning outcomes. Results indicated that fostering observation and questioning skills significantly affects students' cognitive learning achievements. Additionally, both skills were found to have a positive and significant association with learning outcomes. While observation skills displayed a moderate relationship, questioning skills showcased a stronger correlation. Thus, enhancing these skills in science education is crucial for optimizing student learning outcomes.